First record of Pterygodermatites (Pterygodermatites) (Nematoda: Rictulariidae) in South America, with the description of a new species from the Atlantic Forest, southeast Brazil - Simões, Mariana Brandão; Moreira, Narcisa Imaculada Brant; Leite, Yuri Luiz Reis (Zootaxa, 2019)
Pterygodermatites are parasitic nematodes found in mammals worldwide, except Australia. There are 38 described species, which are found parasitizing bats, rodents, marsupials, carnivores and primates. We present taxonomic notes on nematodes collected from the digestive tract of bats from the Atlantic Forest in southeast Brazil. Two species previously recorded in marsupials in this region, Pterygodermatites (Paucipectines) elegans and Pterygodermatites (Paucipectines) jagerskioldi, were found parasitizing molossid and vespertilionid bats, respectively. A new species Pterygodermatites (Pterygodermatites) atlanticaensis found in phyllostomid bats is here described. Despite earlier work based on females, taxonomic work on this group of nematodes is usually based on male characters, such as position and number of caudal papillae, which is a problem because males are short-lived and not easily found. Here we also describe in detail female characters, such as position of the last pair of cuticular processes relative to the posterior end. This is the first record of P. (Pterygodermatites) in South America and the first record of P. (Paucipectines) jagerskioldi in bats.